Reduced expression of the liver/beta-cell glucose transporter isoform in glucose-insensitive pancreatic beta cells of diabetic rats. - Thorens, B (1990)
Rats injected with a single dose of streptozocin at 2 days of age develop non-insulin-dependent diabetes 6 weeks later. The pancreatic beta islet cells of these diabetic rats display a loss of glucose-induced insulin secretion while maintaining sensitivity to other secretagogues such as arginine. We analyzed the level of expression of the liver/beta-cell glucose transporter isoform in diabetic islets by immunofluorescence staining of pancreas sections and by Western blotting of islet lysates. Islets from diabetic animals have a reduced expression of this beta-cell-specific glucose transporter isoform and the extent of reduction is correlated with the severity of hyperglycemia. In contrast, expression of this transporter isoform in liver is minimally modified by the diabetes. Thus a decreased expression of the liver/beta-cell glucose transporter isoform in beta cells is associated with the impaired glucose sensing characteristic of diabetic islets; our data suggest that this glucose transporter may be part of the beta-cell glucose sensor.